Conceptual Understanding of Students Towards COVID-19 Pandemic: Basis for Inclusion in Science, Technology and Society (STS) Curriculum - Dantic, Marshall James (Future Science / FSH-PH Publications, 2022)
The study has utilized a multi-methodology research design with assessment tests and a structured interview guide as instruments in gathering the data. In class 2020, there are 72 students and 8 Teachers of Science, Technology and Society (STS) who served as participants in the study. The assessment test was validated by three experts, Science, Technology and Society teachers with sciences as specialization and a professional education teacher. There are two types of instruments were used to gather data, these are (a) an assessment test and (b) structured interview guide. The assessment test is compose of two parts (I) the traditional multiple choice assessment test that is composed of 20 questions and (II) close-ended essay which consists of five questions. The structured interview guide is composed of one question “In your perspective, should ‘COVID-19 Pandemic’ be included in a STS curriculum? Why?” The results of the study have concluded: level of understanding of the students based from the traditional and essay assessment tests are both fairly satisfactory; level of conceptual understanding based from the relationship between the assessment tests has moderate positive correlation; the perspectives of the teachers regarding the inclusion of COVID-19 Pandemic concept in the STS curriculum, seven themes have emerged. The themes focused on addressing COVID disparities experience across multiple dimension and use it for curriculum formulation and empowerment of STS literacy. The study has recommended; heighten and strengthen the students’ conceptual understanding toward COVID 19 Pandemic through series of topics and teaching approaches; strategically include the concept of COVID-19 pandemic in the curriculum.